PENGARUH KARAKTERISTIK GOOD CORPORATE GOVERNANCE (GCG) TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI PERIODE 2010-2012 - B51110017, STELLA VIVIANTYKA (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2014)
The purpose of this research is to analyze the influence of characteristics of Good Corporate Governance (GCG) on Corporate Social Responsibility (CSR) disclosure in annual reports of Basic Industry and Chemicalsâ€™ corporate that listed on Indonesia Sock Exchange) during 2010-2012. Characteristics that applied in this research are Board of Commissioner size, Independency of Board Of Commissioner, Number of Commissioner meetings, Audit Committee Size, and Number of Audit Committee Meetings. Data analysis method are 1) Statistic Descriptive 2) Classic Assumption Test 3) Examination of Hypothesis with multiple linear regression method. Result of the research indicates that Board of Commissioner size, Independency of Board Of Commissioner, Number of Commissioner meetings, Audit Committee Size, and Number of Audit Committee Meetings do not have a significant effect to Corporate Sosial Responsibility (CSR) disclosure. Keywords: Good Corporate Governance (GCG), Corporate Social Responsibility (CSR),Â  Board of Commissioner, Audit Committee.